The prevalence and diagnostic utility of molecular methods for identifying Entamoeba and Giardia lamblia in Iraq (Open Herald: Periodical of Methodical Research, 2026)
Intestinal parasite infections are the most common cause of infectious disease worldwide, and they have been identified as a public health concern in developing countries. Globally, intestinal Entamoeba histolytica and Giardia lamblia are responsible for amoebiasis and giardiasis, respectively. Although their significant health impact and widespread incidence in Iraq, they receive little attention in terms of prevalence, sensitive diagnostic tools, and associated risk factors. Different techniques for diagnosis are available for detecting intestinal parasites, with microscopic stool testing being the most prevalent and appropriate method. Nonetheless, one limitation is that it lacks the precision of molecular approaches. Therefore, this study aimed to highlight the prevalence of Entamoeba histolytica and Giardia lamblia infections, as well as the molecular detection methods used.